Unveiling the causal link between herpes virus infection and cutaneous leukocytoclastic angiitis: Insights from Mendelian randomization analysis - Heyi Zhang; Jinglei Xie; Yifei Wang; Ruolan Li; Ying Mao; Luyao Song; Zhenyang Yuan; Qinyi Su; Yuehong Huo; Xiaofeng Li; Shengxiao Zhang (Rheumatology & Autoimmunity)
Abstract Background Cutaneous leukocytoclastic angiitis (CLA) is a clinically relevant condition, with previous studies suggesting an association with herpes virus infections. However, the causality of this association remains unclear. This study aimed to investigate the causal relationship between herpes viruses and CLA. Methods Genetic variants linked to the herpes virus were retrieved from the Integrative Epidemiology Unit at the University of Bristol open genome‐wide association studies project and FinnGen database. Data on CLA, involving 262 CLA cases and 207,482 healthy controls, were obtained from the FinnGen consortium R7. Mendelian randomization (MR) analysis, including the inverse variance weighted (IVW), MR‐Egger, and weighted median methods, was performed. Sensitivity analyzes were conducted to ensure the accuracy of the results. Results Of the 15 herpes viruses investigated, only human herpes virus 6 (HHV‐6) demonstrated a causal association with CLA (odds ratio: 1.886, 95% confidence interval: 1.053–3.378, p = 0.033), indicating that HHV‐6 infection significantly increases the risk of CLA. Furthermore, IVW and MR‐Egger tests for heterogeneity confirmed homogeneous MR analysis results without evidence of horizontal pleiotropy (p > 0.05). No significant causal relationship was observed for other herpes viruses, such as herpes simplex virus, varicella‐zoster virus, cytomegalovirus, and Epstein‐Barr virus. Conclusion Our MR analyzes strongly support a causal relationship between HHV‐6 and CLA, elucidating the etiology of this condition and highlighting the potential of HHV‐6‐targeted therapeutic interventions in CLA treatment. However, further research is necessary to expound the underlying mechanisms and explore potential therapeutic interventions targeting HHV‐6‐associated CLA.